Genetics : analysis & principles - Brooker, Robert J. (2021)
"In the seventh edition of Genetics: Analysis & Principles, the content has been updated to reflect current trends in the field. In addition, the presentation of the content has been improved in ways that foster active learning. As an author, researcher, and teacher, I want a textbook that gets students actively involved in learning genetics. To achieve this goal, I have worked with a talented team of editors, illustrators, and media specialists who have helped me to make the seventh edition of Genetics: Analysis & Principles a fun learning tool. Overall, an effective textbook needs to accomplish four goals. First, it needs to provide comprehensive, accurate, and upto- date content in its field. Second, it needs to expose students to the techniques and skills they will need to become successful in that field. Third, an effective textbook should have pedagogical features, such as formative assessment, that foster student learning. And finally, it should inspire students so that they want to continue their studies of genetics and maybe even pursue the field as a career. The hard work that has gone into the seventh edition of Genetics: Analysis & Principles has been aimed at achieving all of these goals"--
Includes index.
Keywords: Genetics